Pengaruh Digital Marketing Dan Electronic Word Of Mouth Terhadap Keputusan Pembelian Produk Ms Glow Men - Ananda, Nickola Wahyu; Wahono, Budi; Khalikussabir, Khalikussabir (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract This research aims to analyze the influence of digital marketing and electronic word of mouth on purchasing decisions for Ms Glow Men products. This research uses quantitative methods with the type of explanatory research. The sample taken was 90 Ms Glow Men consumer respondents at the Islamic University of Malang who were determined using the Malhotra formula. Data analysis using SPSS includes validity test, reliability test, normality test, classical assumption test, hypothesis test, and coefficient of determination test (R2). The results of the research show that digital marketing and electronic word of mouth simultaneously influence the decision to purchase Ms Glow Men products. . Meanwhile, partially digital marketing and electronic word of mouth have a significant influence on purchasing decisions for Ms Glow Men products.  Keywords: Digital Marketing, Electronic Word Of Mouth, Purchasing Decisions